2011
DOI: 10.1186/alzrt75
|View full text |Cite
|
Sign up to set email alerts
|

Masitinib as an adjunct therapy for mild-to-moderate Alzheimer's disease: a randomised, placebo-controlled phase 2 trial

Abstract: IntroductionNeuroinflammation is thought to be important in Alzheimer's disease pathogenesis. Mast cells are a key component of the inflammatory network and participate in the regulation of the blood-brain barrier's permeability. Masitinib, a selective oral tyrosine kinase inhibitor, effectively inhibits the survival, migration and activity of mast cells. As the brain is rich in mast cells, the therapeutic potential of masitinib as an adjunct therapy to standard care was investigated.MethodsA randomised, place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(130 citation statements)
references
References 30 publications
(42 reference statements)
2
127
0
1
Order By: Relevance
“…Additionally, it has been demonstrated that fibrillar amyloid beta peptides are capable of directly activating the mast cells through a CD47/beta 1-integrin membrane complex to elicit mast cell degranulation, suggesting that mast cells may play a major role in AD pathogenesis (Niederhoffer et al 2009). Very recently, administration of masitinib mesilate, a selective tyrosine kinase inhibitor and efficient in controlling the survival, differentiation, and degranulation of mast cells, has been shown to slow cognitive decline in AD patients in phase II clinical trial (Piette et al 2011).…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Additionally, it has been demonstrated that fibrillar amyloid beta peptides are capable of directly activating the mast cells through a CD47/beta 1-integrin membrane complex to elicit mast cell degranulation, suggesting that mast cells may play a major role in AD pathogenesis (Niederhoffer et al 2009). Very recently, administration of masitinib mesilate, a selective tyrosine kinase inhibitor and efficient in controlling the survival, differentiation, and degranulation of mast cells, has been shown to slow cognitive decline in AD patients in phase II clinical trial (Piette et al 2011).…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Accordingly, clinical trials have shown therapeutic effects of masitinib in cases of mastocytosis, a rare disease characterized by abnormal accumulation and activation of mast cells in various tissues and organs (28). Masitinib was also shown to beneficially modulate CNS function in multiple sclerosis (29), stroke (30), and Alzheimer' s disease (31). In addition, a recent phase III clinical trial with masitinib in ALS has shown promising therapeutic effects in a significant group of patients, slowing the deterioration of motor functions and reducing the decline in quality of life (32).…”
Section: Introductionmentioning
confidence: 99%
“…No safety issues related to Cerebrolysin were indicated by the study's conclusion. As a result of the relative success of this trial, Ever Neuro Pharma GmbH is moving forward with a phase 4 study to compare the efficacy of Cerebrolysin to that of donepezil (NCT01822951) set to begin September 2013 (7). …”
Section: Currently Active Late-stage Trialsmentioning
confidence: 99%